Evaluation the inhibitory effect of nicardipine on the metabolism of quetiapine - Yang, Jinzhao; Xia, Hailun; Li, Qingqing; Li, Ruibin; Cao, Lu; Tang, Congrong (Frontiers in Pharmacology, 2025)
The aim of this study was to investigate the impact of calcium channel blockers (CCBs) and antihypertensive traditional Chinese medicine (TCM) on the metabolism of quetiapine. In vitro, two incubation systems of rat liver microsomes (RLM) and human liver microsomes (HLM) were established and optimized to explore potential interactions between five kinds CCBs (nicardipine, dilthiazem, lercanidipine, nimodipine, nitrendipine), five kinds antihypertensive TCM (quercetin, fangchinoline, apigenin, tetrandrine, and berberine) and quetiapine, and to evaluate their underlying inhibition mechanisms. In vivo, Sprague-Dawley rats were used to assess the interaction between quetiapine and nicardipine. The results showed that nicardipine had the highest inhibition rate (79.22%) against quetiapine metabolism among those drugs screened. The half-maximal inhibitory concentration (IC50) values for the inhibition of quetiapine metabolism by nicardipine in RLM and HLM were similar, at 10.29 ± 0.06 μM and 13.23 ± 0.37 μM, respectively. In RLM, nicardipine exhibited a mixed mechanism of competitive and non-competitive inhibition, while in HLM, it displayed a non-competitive and un-competitive inhibition mechanism. In vivo results indicated that nicardipine could significantly increase the main pharmacokinetic parameters AUC(0-t), AUC0−∞, and Cmax of quetiapine, but decrease the AUC(0-t) of its metabolite N-desalkylquetiapine. The findings of this study suggested that nicardipine had inhibited the metabolism of quetiapine, suggesting the dose adjustment or therapeutic drug monitoring of quetiapine should be conducted to achieve individualized therapy.